'PC worlds': Ethno-nationalist identitarian theories of anti-political correctness. (March 2021) - Trémon, Anne-Christine
Over the past two decades, politicians and intellectuals have lent support to rising anti-immigrant sentiments, ethno-nationalist integralism and far-right populism by coining expressions such as 'cultural exclusion' and claiming to be speaking in the name of the 'people', often under cover of anti-political correctness. In this article I identify a series of recurrent features of such ethno-nationalist identitarian theories. The book I am critiquing, PC Worlds: Political Correctness and Rising Elites at the End of Hegemony (2019) by Jonathan Friedman, is a clear example of these trends. The scholar who had previously critiqued racialized politics and the reification of cultures now offers a book in favour of anti-immigrant ethno-nationalism and radical cultural othering. The article shows how this is the result of contradictions related to the evolution in his own thinking and situates these contradictions in regard to different theories of the nation-state. It also demonstrates how Friedman has proceeded to hollow out his own previous model, by making a distorted and normative use of it, and points out a number of weaknesses, particularly regarding the notions of 'elites' and 'hegemony'. Finally, it questions the very project of conducting a study of political correctness.